'Pathetic earthlings! Who can save you now?' Science fiction, planetary crisis and the globalisation of Chinese culture. Issue 1 (March 2022) - Hartley, John
Chinese policy has turned to the globalisation of communication and stories. Beyond the diplomatic 'voice', one of the ways that Chinese culture is reaching out to the rest of the world is through science fiction. Sci-fi can be construed as a specialist thinking-circuit for cultures to build and explore experimental models of collective action at global and planetary scale. What do its stories tell us about the globalisation of Chinese culture? When the need to 'save the world' has crossed over from sci-fi to science, from entertainment to activism, and from a thought experiment to imminent danger, humans as a whole face challenges of their own making: climate change, environmental pollution, pandemics, extinctions, exclusions and nuclear annihilation. Can sci-fi inspire collective action at species scale? What role will globalising China play?